Multi-domain Modelling in DESTECS and Ptolemy - a Tool Comparison - Wolff, Sune; Pierce, Ken; Derler, Patricia (Technical Report Electronics and Computer Engineering, 2013)
Developing embedded systems with high performance and safety requirements is notoriously hard. It is not enough to have a thorough understanding of the control algorithms used, but a deep understanding of the monitored and controlled physical environment is required to ensure that performance and safety requirements are met. Various tools deal with modeling such multi-domain systems and provide evaluation through simulation. Two such tools — DESTECS and Ptolemy — are examined and compared in this paper, using a case study of an aircraft fuel system. Usability, quantitative, and qualitative comparison criteria are used to give a thorough analysis of the capabilities of the two tools. The contribution of this paper is a description of pros and cons of each tool, helping future users to choose the right tool that suits their needs.